Safety and efficacy of contemporary catheter ablation for atrial fibrillation patients with a history of cardioembolic stroke in the era of direct oral anticoagulants. Issue 1 (July 2017) - Nishizaki, Kimitaka; Itoh, Taihei; Kimura, Masaomi; Tsushima, Yuichi; Shoji, Yoshihiro; Kinjo, Takahiko; Ishida, Yuji; Sasaki, Kenichi; Horiuchi, Daisuke; Sasaki, Shingo; Tomita, Hirofumi; Okumura, Ken
Abstract: Background: The safety and efficacy of the contemporary atrial fibrillation (AF) ablation in patients with a recent or previous history of cardioembolic stroke (CS) or transient ischemic attack (TIA) remain to be established. Methods: A total of 447 patients who underwent first-ever contact force (CF)-guided AF ablation with circumferential pulmonary vein isolation were included. Of these, 17 had CS or TIA within 6 months before ablation (Group 1), 30 more than 6 months before ablation (Group 2), and the other 400 without CS or TIA (Group 3). Procedural complications and recurrence of AF and atrial tachyarrhythmias were compared among the 3 groups. Results: The mean age was 71 ± 7, 66 ± 9, and 61 ± 11 years in Groups 1, 2, and 3, respectively ( p  < 0.05, Group 1 versus Group 3). The oral anticoagulants were warfarin ( n  = 108, 24.1%), dabigatran ( n  = 101, 22.6%), rivaroxaban ( n  = 147, 32.9%), apixaban ( n  = 87, 19.5%), and edoxaban ( n  = 4, 0.9%), and did not differ among the 3 groups. Median follow-up period was 14 [IQR 12–22], 13 [12–14], and 12 [10–16] months, respectively. One episode of cardiac tamponade, 2 episodes of arteriovenous fistula, and some minor complications occurred in Group 3, but no complications occurred in Groups 1 and 2 in the periprocedural period. Although one episode of CS occurred 11 days after the procedure in Group 3, there were no periprocedural CS, TIA, or major bleedings in Groups 1 and 2. AF recurrence-free rate after the procedure was 76.5%, 86.7%, and 79.1% in Groups 1, 2, and 3, respectively, and there was no difference in Kaplan–Meier curves among the 3 groups. Conclusion: The safety and efficacy of CF-guided AF ablation in the era of direct oral anticoagulants in patients with a recent or previous history of CS or TIA are similar to those in patients without it.